Addressing diversity in literacy instruction - Ortlieb, Evan; Cheek, Earl H. (Bingley, U.K. : Emerald Publishing Limited, 2017)
This book presents recent research related to how issues of diversity are addressed within literacy instruction for K-12 learners. Over the last decade, issues of diversity have promulgated within the field of literacy. Recent revisions to teacher education standards call for new approaches to professional development to ensure that educators are positioned to view and utilize diversity as an advantage within their classrooms and notions of what constitutes diversity are expanding. As the population of learners continues to diversify, literacy teachers must be equipped with knowledge of who their learners are and how to effectively build upon their individual experiences, lifestyles, and ways of seeing the world. A systematic change is needed and this volume is directed at advancing research within the intersectionality between literacy and diversity to contribute towards this important mission. This volume features prominent literacy researchers sharing their evidence-based successes that are founded upon longstanding and newfound theoretical frameworks. It is suitable for both educators in K-12 and university classroom contexts for teachers, administrators, graduate students, and professors alike.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Literacy -- Social aspects; Multicultural education